Online Payment and Consumers’ Attitude towards Risk reduction strategies in a cash based economy - Iriobe, Ofunre Chukwudi (Archives of Business Research, 2018)
Online payment for goods has grown globally; unfortunately, the advancement in technology has not lowered the level of perceived risk felt by customers who pay for products online. The adoption of online payment in Nigeria is still low hence, consumers are given options considered less risky to use. Many online vendors have adopted different risk reducing strategies to help curb the perceive risk felt by customers when paying online. The effect of these risk reducing factors have not been adequately investigated in Nigeria especially, given that online vendors in Nigeria accommodate buying online and paying cash. Using a sample of 170 young people in Nigeria, an ordered logistic regression was used to test the relationship between various risk-reducing strategies such as Money Back Guarantee (MBG), Electronic Word of Mouth (EWOM), Informational Influence (IIF) and Pay on Delivery (POD) in Nigeria and customers’ attitude towards electronic payment (CAT). We found that MBG, EWM and POD have significant positive influence on (CAT) while IIf exhibited a significant negative influence. The various risk reduction strategies employed by the study contributes a significant 12% to the variation of customers’ attitude towards electronic payment. We concluded that risk reduction strategies have a significant positive impact on customers’ attitude towards electronic payment in Nigeria. Hence, we recommend that online vendors should encourage more interpersonal online interaction among users, they should also provide more money back guarantees and pay-on-delivery offers to consumers to simulate and hasten their movement from traditional payment methods to online payment methods.